What Stops Us from Performing More Pacemaker Electrodes Extractions? - Barbosa, Rodrigo Minati (JOURNAL OF CARDIAC ARRHYTHMIAS, 2023)
Lead extraction is a challenging procedure and needs to be performed by more centers throughout Brazil. The reasons for the underuse of the procedure and the necessary actions needed to be taken by the medical community are discussed in the text.